The Austin Friars in pre-Reformation English society - Laferriere, A (2017)
This study examines the role of the Austin Friars in pre-Reformation English society, as distinct both from the Austin Friars of Europe and from other English mendicant orders. By examining how the Austins formulated their origins story in a distinctly English context, this thesis argues that the hagiographical writings of the Austin Friars regarding Augustine of Hippo, whom they claimed as their putative founder, had profound consequences for their religious platform. As their definition of Augustine’s religious life was less restrictive than that of the European Austin Friars and did not look to a recent, charismatic leader, such as Dominic or Francis, the English Austin Friars developed a religious adaptability visible in their pastoral, theological, and secular activity. This flexibility contributed to their durability by allowing them to adapt to religious needs as they arose rather than being constrained to what had been validated by their heritage. The behaviour of these friars can be characterised foremost by their ceaseless advancement of the interests of their own order through their creation of a network of influence and the manoeuvring of their confrères into socially and economically expedient positions. Given the propensity of the Austin Friars towards reform, this study seeks to understand its place within and interaction with English society, both religious and secular, in an effort to reconstruct the religious culture of this order. It therefore investigates their interaction with the laity and patronage, with heresy and reform, and with secular powers. It emphasises, above all, the distinctiveness of the English Austin Friars both from other mendicant orders and from the European Austin Friars, whose rigid interpretations of the religious example of Augustine led them to a strict demarcation of the Augustinian life as eremitical in nature and to hostile relations with the Augustinian Canons. Ultimately, this thesis interrogates the significance of being an Austin Friar in fifteenth- or sixteenth-century England and their role in the religious landscape, exploring the exceptional variability to their behaviour and their ability to take on accepted forms of behaviour.